2022
DOI: 10.3390/jcm11071954
|View full text |Cite
|
Sign up to set email alerts
|

Can Cognitive Flexibility and Clinical Perfectionism Be Used to Identify People with Anorexia Nervosa?

Abstract: Poor cognitive flexibility and perfectionism are common features in anorexia nervosa (AN). The current study aimed to investigate cognitive flexibility and clinical perfectionism as potential predictors of AN. Twenty women with a current diagnosis of AN (M age = 28.25, SD = 7.62) and 170 community participants with no lifetime history of an eating disorder (M age = 29.23, SD = 9.88) took part in an online cross-sectional study that included self-report questionnaires of cognitive flexibility and clinical perfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it was described several years ago how anorexia patients could present anxiety persistence, perfectionism, and obsessional behaviors, including symmetry, exactness, and order [12][13][14]. Nowadays, researchers point out how female anorexia patients self-report significantly lower cognitive flexibility and significantly higher clinical perfectionism [15]. In this study, participants self-reported in a questionnaire which evaluated different items, including cognitive, behavioral and affective components of setting aims and struggling to achieve them, as well as the consequences on their self-evaluation when these principles were accomplished or not accomplished [16].…”
Section: Psychological Profilementioning
confidence: 99%
“…Furthermore, it was described several years ago how anorexia patients could present anxiety persistence, perfectionism, and obsessional behaviors, including symmetry, exactness, and order [12][13][14]. Nowadays, researchers point out how female anorexia patients self-report significantly lower cognitive flexibility and significantly higher clinical perfectionism [15]. In this study, participants self-reported in a questionnaire which evaluated different items, including cognitive, behavioral and affective components of setting aims and struggling to achieve them, as well as the consequences on their self-evaluation when these principles were accomplished or not accomplished [16].…”
Section: Psychological Profilementioning
confidence: 99%
“…Of particular interest would be research on specific clinical populations or profiles, such as patients with eating disorders, who report lower levels of outcome improvement and satisfaction with hospital care. It may be suggested that, more than in other groups of patients, the subjective well-being of patients with eating disorders depends on factors other than symptom improvement, for example, interfering personality traits such as “perfectionism” [ 62 ]. Exploring this hypothesis could shed valuable light on how to adapt clinical care strategies and interventions accordingly for this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Perfectionism is a personality trait that reflects the tendency to have very high personal standards, be overly critical of oneself when these standards are not achieved, have an extreme preoccupation with mistakes, doubt when considering personal achievements, and have an excessive focus on organization and precision [ 9 ]. Higher levels of perfectionism are consistently found in adolescents and adults with AN compared to healthy controls [ 10 , 11 , 12 ] and may be a risk factor for longer illness duration [ 13 ]. Perfectionism has also been associated with feeling the need for control over the self and body [ 14 ].…”
Section: Introductionmentioning
confidence: 99%